Development and validation of a questionnaire on knowledge, attitudes and practice on healthy lifestyle for Malaysian adolescents in school hostels - Hiew, Chu Chien (2015)
Instruments to assess knowledge, attitude and practice (KAP) on healthy lifestyle of adolescents are limited. This study aims to develop and determine the validity and reliability of the Knowledge, Attitude and Practice on Healthy Lifestyle Questionnaire (KAP-HLQ) among Malaysian adolescents living in secondary school hostels. A cross-sectional study which involved 647 lower secondary school students from 12 school hostels in Malaysia was conducted to determine construct validity, internal consistency reliability and test-retest reliability of the KAP-HLQ. The initial set of the KAP-HLQ consisted of 56 knowledge items, 62 attitude items and 60 practice items. Items were developed mainly based on the Healthy Eating and Active Living among Teens (HEBAT) intervention module under the Healthy Lifestyle Program. From the content validity, an expert panel agreed upon eliminating 14 knowledge items, and one item each from the attitude and practice sections due to inappropriateness of items. This results in retaining 42 knowledge items, 61 attitude items and 59 practice items. Several items were revised based on the feedbacks from a separate pool of 36 respondents during the determination of face validity. In performing construct validity through exploratory factor analysis, four dimensions were identified for the attitude section consisting 27 items and six dimensions were identified for the practice section consisting 28 items. In addition, convergent validity was determined by correlating knowledge and attitude (r=0.260, p<0.05), knowledge and practice (r=0.201, p<0.05), and attitude and practice (r=0.517, p<0.05) on healthy lifestyle. These indicate that those who have good knowledge in healthy lifestyle have positive attitudes and do practice healthy lifestyle. The internal consistency coefficients for the KAP sections of the KAP-HLQ instrument were 0.654, 0.845 and 0.636 respectively, indicating that it is a reliable tool to assess KAP towards healthy lifestyle of the target group. Furthermore, test-retest reliability of the KAP-HLQ was determined among a subset of adolescents (n=118) at two time points with an interval of two weeks (knowledge: r=0.631, p<0.05; attitude: r=0.358, p<0.05; practice: r=0.481, p<0.05). The significant correlations indicate the repeatability of the instrument. The final set of the KAP-HLQ consisted of 42 knowledge items (possible score: 0-42) 27 attitude items (possible score 27-135) and 28 practice items (possible score: 28-140). Knowledge on healthy lifestyle can be assessed by total knowledge score, while attitude and practice on healthy lifestyle can be assessed by total score and by dimensions. The mean total knowledge, attitude and practice on healthy lifestyle scores obtained by the respondents were 19.7±4.9, 97.9±12.4 and 90.0±10.0, respectively. This KAP-HLQ has been validated and tested for its reliability, thus should act as a useful tool to determine the knowledge, attitude and practice on healthy lifestyle among adolescents living in school hostels. It is recommended that the KAP-HLQ can be further improved to measure more aspects of healthy lifestyle. Besides, validation should be done if used among other populations.